PERAN MUSYRIF TAHFIDZ SEBAGAI MOTIVATOR DALAM MENINGKATKAN KEMAMPUAN MENGHAFAL MAHASANTRI MA’HAD ‘ALY BAITUL QUR’AN WONOGIRI - Muhamad Abdul Azis; Joko Subando (Lembaga Pengembangan Inovasi Pendidikan Baiturrahman, 2025)
This study aims to explore the role of musyrif tahfidz as a motivator in improving students' ability to memorize the Qur'an. Using a descriptive qualitative approach, data were collected through observation, interviews, and documentation. The results show that musyrif tahfidz acts as both an internal and external motivator through exemplary behavior, spiritual guidance, and constructive encouragement. This role has been proven to enhance the quality and quantity of students’ Qur’anic memorization.